Mobility and diet in Prehistoric Denmark: strontium isotope analysis and incremental stable isotope analysis of human remains from the Limfjord area - van der Sluis, LG; Daly, JS; Frei, KM; Reimer, PJ (Danish Journal of Archaeology, 2020)
The Limfjord in Denmark held a prominent position throughout Prehistory as a natural communication port between east and west. Identifying the presence of non-local individuals might shed light on socio-economic and cultural changes occurring in the Limfjord area. Existing studies attempting to do so using strontium isotope analysis on Danish prehistoric remains focus on certain archaeological time periods and geographic locations, resulting in an uneven distribution of analysed material. This study aimed at filling a gap in the existing literature, both from a geographical as well as a chronological point of view. Additionally, carbon and nitrogen stable isotope analysis on bone and tooth dentine from these individuals was carried out to examine dietary changes between childhood and adulthood. The strontium isotope results revealed four non-local individuals, two from the Neolithic, one from the Early Roman Iron Age and one from the Germanic Iron/Viking Age. We conducted incremental stable isotope analysis of tooth dentine from the four non-local individuals to investigate the palaeodietary information in their dental records at a higher resolution and potentially pinpoint their age at the time of movement. The two Neolithic individuals revealed stable isotope ratios that might be indicative of stress.